Social Web Applications as Means to Enhance Lifelong Learning and Professional Development of Teachers: A Tool to Support Assessment of Their Impact - Andreas Koskeris; Georgia Boura; John Garofalakis (European Scientific Journal, ESJ, 2020)
The application of new technologies in classroom has made the need for constant professional development more important for teachers. They should be able to keep up with the technological development in the classroom. Their professional development includes constant upgrade of their skills and knowledge on how they can meet the needs of their students or address issues derived from ICTs application in classroom. Social Web applications are providing new opportunities to build and gain such professional development by assisting to remain current on skills and issues important for a professional role. Aim of the present work is to contribute to the assessment of impact of Social Web applications for teachers’ professional development by presenting specific case studies and proposing an ICT tool to be used for the collection of useful quantitative indicators supporting this impact assessment. The assesment derived from a specific showcase of its application, provided real case results on the usage of Social Web tools from teachers which could be a useful asset towards the design of teacher training programs for the effective use of social networking tools.